2005
DOI: 10.1007/s00406-005-0578-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treatment on serum brain–derived neurotrophic factor levels in depressed patients

Abstract: Researchers have reported that serum brain-derived neurotrophic factor (sBDNF) of drug-free depressed patients are lower than those of healthy controls and proposed that low sBDNF levels might reflect failure of neuronal plasticity in depression. In this study, we compared sBDNF levels of depressed patients (n = 28) before and after 8 weeks of antidepressant treatment, with those of healthy controls (n = 18) to test the hypothesis that initially low sBDNF levels of drug-free depressed patients will increase pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
185
3
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(212 citation statements)
references
References 44 publications
19
185
3
5
Order By: Relevance
“…All of these treatments increase BDNF at least in rats, and likely in humans, as supported by multiple threads of evidence, e.g., direct measurements of BDNF in the bloodstream (Karege et al 2002(Karege et al , 2005Shimizu et al 2003). Treatment of depressed patients with antidepressants increases the reduced pretreatment serum BDNF levels close to the levels of normal controls (Aydemir et al 2005;Gervasoni et al 2005;Gonul et al 2005). Some results suggest that the combination of exercise and antidepressant treatment may have significant neurochemical and behavioural effects.…”
Section: Neurotrophic Factorsmentioning
confidence: 93%
“…All of these treatments increase BDNF at least in rats, and likely in humans, as supported by multiple threads of evidence, e.g., direct measurements of BDNF in the bloodstream (Karege et al 2002(Karege et al , 2005Shimizu et al 2003). Treatment of depressed patients with antidepressants increases the reduced pretreatment serum BDNF levels close to the levels of normal controls (Aydemir et al 2005;Gervasoni et al 2005;Gonul et al 2005). Some results suggest that the combination of exercise and antidepressant treatment may have significant neurochemical and behavioural effects.…”
Section: Neurotrophic Factorsmentioning
confidence: 93%
“…The resultant decrease in activity in excitatory neurons could underlie the observed downregulation of BDNF. Moreover, several studies have shown that SSRI treatment, which increases synaptic serotonin levels, can reverse the stress-induced downregulation of BDNF gene expression (Aydemir et al, 2005;Gervasoni et al, 2005;Gonul et al, 2005). In summary, stress generally inhibits BDNF gene expression, and some evidence suggests that this effect is, at least in part, mediated by a reduction in serotonin signaling.…”
Section: Stressmentioning
confidence: 98%
“…[50][51][52] Furthermore, serum BDNF in living depressed patients is abnormally low, but can be restored following pharmacological antidepressant treatment. [53][54][55][56][57][58] The BDNF hypothesis of depression: the argument against…”
Section: Clinical Evidencementioning
confidence: 99%